A comparative evaluation of Korean MMPI‐A and MMPI‐A‐RF Substance Abuse Scales. Issue 12 (6th August 2019) - White, Jacob V.; Han, Kyunghee; Weed, Nathan C.; Lim, Jeeyoung; Moon, Kyungjoo; Yook, Keunyoung; Kim, Ji‐Hae
Abstract: Objective: The purpose of the present study was to compare psychometric properties of the Substance Abuse (SUB) Scale on the Korean Minnesota Multiphasic Personality Inventory–Adolescent‐Restructured Form (MMPI‐A‐RF) with those on the Korean MMPI‐A (the Alcohol/Drug Problem Acknowledgment Scale [ACK]), the Alcohol/Drug Problem Proneness Scale [PRO], and the MacAndrew Alcoholism Scale‐Revised Scale [MAC‐R]). Method: Participants consisted of 237 Korean adolescent psychiatric patients whose scores on these measures were compared in terms of internal consistency and predictive validity. Results: Scores on SUB exhibited superior internal consistency to that of the MMPI‐A substance abuse scales. Further, scores on SUB predicted substance abuse more accurately than did the optimal combination of scores on the MMPI‐A substance abuse scales. Conclusion: Results provide strong support for the use of the Korean MMPI‐A‐RF SUB scale when assessing substance abuse in Korean youth.